Walking in Cities : Quotidian Mobility as Urban Theory, Method, and Practice - Shortell, Timothy; Brown, Evrick (Book collections on Project MUSE., 2016)
"Walking connects the rhythms of urban life to the configuration of urban spaces. As the contributors and editors show in Walking in Cities, walking also reflects the systematic inequalities that order contemporary urban life. Walking has different meanings because it can be a way of temporarily "taking possession" of urban space, or it can make the relatively powerless more vulnerable to crime. The essays in Walking in Cities explore how walking intersects with sociological dimensions such as gender, race and ethnicity, social class, and power. Various chapters explorethe fl & acirc;neuse, or female urban drifter, in Tehran's shopping malls; Hispanic neighborhoods in New York, San Diego, and El Paso; and the intra-neighborhood and inter-class dynamics of gentrification in Greenpoint, Brooklyn. The essays in Walking in Cities provide important lessons about urban life"